2004
DOI: 10.1158/0008-5472.can-04-1517
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Extracellular-signal Regulated Kinases 1/2 Is Required for Apoptosis of Human Colon Cancer Cells In vitro by Sulindac Metabolites

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) including sulindac have shown potent chemopreventive and tumor regressive effects against colorectal cancer, the second leading cause of cancer death in the United States. However, the mechanisms by which sulindac inhibits tumor cell growth are not completely understood. We previously reported that sulindac metabolites inhibit the mitogen-activated protein/extracellular signal-regulated kinase kinase/extracellular signal-regulated kinase (MEK/ ERK) signaling cascad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 18 publications
2
35
0
3
Order By: Relevance
“…35,36) In this study, we showed that etodolac inhibits HGF-and 10% FBS-in- duced ERK activity and proliferation of HCC cells. This finding showed that a COX-2 inhibitor might inhibit HCC cell proliferation by interfering with growth signals mediated by growth factors.…”
Section: )mentioning
confidence: 54%
“…35,36) In this study, we showed that etodolac inhibits HGF-and 10% FBS-in- duced ERK activity and proliferation of HCC cells. This finding showed that a COX-2 inhibitor might inhibit HCC cell proliferation by interfering with growth signals mediated by growth factors.…”
Section: )mentioning
confidence: 54%
“…This was then substantiated by the finding that similar synergistic effects were obtained when the cells were exposed to oxaliplatin followed by C225 (an antibody inhibitor of EGFR) or UO126 (an inhibitor of MEK1). In addition, maintenance of the G 2 -M block and potentiation of apoptosis by the OXA-ZD6474 sequence were completely blocked in HT29-MEK1 (R4F) cells expressing a constitutively active form of MEK (44). Together, these data strongly suggest that the antitumor synergistic interaction between oxaliplatin and ZD6474 depends, in large part, on reversal of ZD6474-mediated antagonism of the activation of the EGFR prosurvival pathway by oxaliplatin.…”
Section: Discussionmentioning
confidence: 79%
“…8). Second, we made use of HT29 cells (R4F) that stably expressing a constitutively active form of MEK1 (44). The R4F cells when treated with the OXA-ZD6474 sequence both failed to undergo apoptosis (Fig.…”
Section: Oxaliplatin and Zd6 474 Interaction Is Egfr Dependentmentioning
confidence: 99%
“…Moreover, restoration of intracellular polyamine concentrations prevented sulindac-induced cell death in those tumors (37). Also, inhibition of extracellular signalregulated kinase 1/2 is absolutely required for the apoptotic effect of exisulind (38,39). Hence, signaling mechanisms other than those dependent on cGMP mediate the antineoplastic effects of exisulind in colon cancer.…”
Section: Discussionmentioning
confidence: 99%